Experimental Study on Bending Moment of Double-Row Steel Pipe Piles in Foundation Excavation - Ming-yi Zhang; Jia-xiao Ma; Shu-juan Yang; Yong-hong Wang; Xiao-yu Bai; Shao-xia Sun (Advances in Civil Engineering)
Double-row steel pipe piles have been widely used in retaining and protection of foundation excavation because of the advantages of high bearing capacity, high flexural rigidity, fast construction speed, and so on. This study presents a field test to assess the feasibility of strain gauges in monitoring the strain of double-row steel pipe piles during foundation excavation. Two steel pipe piles were instrumented with strain gauges and then installed into the drilling holes. The installation method of strain gauges is introduced first. Then, the bending moment of the test piles during the foundation excavation was analyzed. The field test results indicate that the survival rate of strain gauges was 100%, and the monitoring method used in the test was feasible to measure the bending moment of double-row steel pipe piles. Moreover, with the increase in foundation excavation depth, the bending moment of the test piles all increased, and the bending moment of the inner pile was obviously higher than that of the outer pile. The bending moment distribution of the whole support system accords with the conventional pile-anchor mode. The test results can provide reference and basis for the design and construction of double-row steel pipe piles.